The Effect of Brand Hate on Non-repurchase Intention with Variety Seeking Behavior as Moderating Variable - Syahrinabila Pulungan; Teguh Widodo (Lafadz Jaya Publisher, 2023)
The purpose of this study is to examine the relationship between brands and consumers in a negative perspective that focuses on consumer behavior, such as purchase decisions by contributing to adding variables that can moderate the relationship between brand hate and non-repurchase intention, namely variety seeking behavior. The existence of a tendency for people to choose variety makes it important for researchers to use the variable seeking behavior to see its moderating effect on the non-repurchase intention. The population used in this study are e-commerce users in the five major cities in Indonesia. The sample selection technique uses purposive sampling. Data were collected through survey shared by Sosial Media. Data is processed using SMART-PLS 3.2.9. The results shows that brand hate has a positive effect on NWOM, Online Complaining and Non-repurchase intention. NWOM has a positive effect on non-repurchase intention. Online complaining has no effect on non-repurchase intention. Variety seeking behavior does not moderate the relationship between brand hate, NWOM, online complaining and non-repurchase intention.